USING POSTER AS MEDIA TO TEACH SPEAKING SKILL FOR THE SEVENTH GRADE STUDENTS OF SMPN 1 KAWEDANAN - Windy Eka Yuliantari; S Sumani; Erlik Widiyani (English Teaching Journal : A Journal of English Literature, Language and Education, 2017)
The Researcher focuses on implementing of Poster as media to teach peaking. This research has some purpose, the purpose of this research are: (1) to describe the implementation of using Poster as media (2) to identify advantages of using Poster as media (3) to describe disadvantages of using Poster as media (4) to identify problem arised of using Poster as media. In this research, the researcher uses qualitative research as research approach in doing this research in order to answer the problem of the teaching speaking by using Poster. Type  of this research is descriptive research. The technique of collecting data are observation, interview, and documentation. There are three sources of the data there are participant, social situation and document. There are four results of teaching speaking by using Poster as media. First, the student can be active in speaking English. Second, the students are fun. Third, media can be alternative learning to teach speaking. Fourth, the students get new experience when they do presentation in front of the class. The disadvantages of implementing Poster as media are, ‘it takes a lot of the time and students have not known the character on the poster. In this research the solutions  that are the students may do anything to get information to make sentence and using famous character. The Researcher conclude that the media is effective in teaching speaking because the students get new learning and the students can be brave to speak English. The suggestion are (1) The students are suggested to practice their speaking and to work with the other students. (2) The teacher must be more creative to find the alternative ways in teaching and learning process. (3) The institution has a great role to stimulate the students of institution in speaking ability. (4) Future Researcher hopes that the future researcher to be more creative in making the research on Poster as Media to teach speaking english.